Preparo de fotoanodos a base de tio2 sensibilizados por pontos quânticos para aplicação em células fotovoltaicas - Rosa, Lucas Tadeu Aparecido Da (2019)
One of the major challenges facing humanity is the development of new forms of renewable energy. The use of solar energy is a promising alternative, with potential to meet all current demand. To this end, the development of the first generations of solar cells was started, and the creation of dye solar cells in the 90s made possible the expansion of the model so that other sensitizing agents could be used, such as quantum dots (QDs). The aim of the present work was to optimize the synthesis of QD cadmium telluride (CdTe) in aqueous medium and to assess the influence of pH, solvent, surface stabilizer (SS) and the Cd:SS ratio, which enabled the quantum yield of photoluminescence to be used in photoanodes. The synthesized QDs were characterized by UV-vis spectroscopy, photoluminescence, infrared, dynamic light scattering, radioactive decay and X-rays, besides transmission electron micrograph (TEM), Zeta potential and thermogravimetric analysis. In the second step, the synthesized QDs acted as sensitizing agents in photoanodes for use in photovoltaic cells, what analyzed by linear voltammetry and chronoamperometry. The QDs presented significant variations in the optical properties as a function of the variation of the reaction medium and the molar ratio of the surface stabilizer. The best results were obtained for the molar ratio Cd:TGA (thioglycolic acid) of 1:1.5, in medium formed by water + glycerin and water, respectively. As reference for the assembly of the solar cells, CdS (cadmium sulfide) was used as a sensitizing QD, presenting satisfactory results. However, sensitization of the photoanode with CdTe QDs was not achieved due to problems with the interaction between TiO2 (titanium dioxide) and CdTe, with results approaching the absence of sensitizing agent.